Interactions Between Neuropsychiatric Symptoms and Alzheimer's Disease Neuroimaging Biomarkers in Predicting Longitudinal Cognitive Decline - Pink, Anna; Krell-Roesch, Janina; Syrjanen, Jeremy A; Christenson, Luke R; Lowe, Val J; Vemuri, Prashanthi; Fields, Julie A; Stokin, Gorazd B; Kremers, Walter K; Scharf, Eugene L; Jack, Clifford R; Knopman, David S; et al. (Psychiatric research and clinical practice, 2023)
OBJECTIVE: To examine interactions between Neuropsychiatric symptoms (NPS) with Pittsburgh Compound B (PiB) and fluorodeoxyglucose positron emission tomography (FDG-PET) in predicting cognitive trajectories. METHODS: We conducted a longitudinal study in the setting of the population-based Mayo Clinic Study of Aging in Olmsted County, MN, involving 1581 cognitively unimpaired (CU) persons aged ≥50 years (median age 71.83 years, 54.0% males, 27.5% APOE ɛ4 carriers). NPS at baseline were assessed using the Neuropsychiatric Inventory Questionnaire (NPI-Q). Brain glucose hypometabolism was defined as a SUVR ≤ 1.47 (measured by FDG-PET) in regions typically affected in Alzheimer's disease. Abnormal cortical amyloid deposition was measured using PiB-PET (SUVR ≥ 1.48). Neuropsychological testing was done approximately every 15 months, and we calculated global and domain-specific (memory, language, attention, and visuospatial skills) cognitive z-scores. We ran linear mixed-effect models to examine the associations and interactions between NPS at baseline and z-scored PiB- and FDG-PET SUVRs in predicting cognitive z-scores adjusted for age, sex, education, and previous cognitive testing. RESULTS: Individuals at the average PiB and without NPS at baseline declined over time on cognitive z-scores. Those with increased PiB at baseline declined faster (two-way interaction), and those with increased PiB and NPS declined even faster (three-way interaction). We observed interactions between time, increased PiB and anxiety or irritability indicating accelerated decline on global z-scores, and between time, increased PiB and several NPS (e.g., agitation) showing faster domain-specific decline, especially on the attention domain. CONCLUSIONS: NPS and increased brain amyloid deposition synergistically interact in accelerating global and domain-specific cognitive decline among CU persons at baseline.